OPTIMIZATION BUILDING ENCLOSURE REDESIGN TO FULFILL NATURAL LIGHTING INTENSITY STANDARD AND OTTV IN SOUTH QUARTER JAKARTA OFFICE BUILDING BASED ON GREENSHIP CRITERIA - Santoso (Jurnal Riset Arsitektur, 2019)
Abstract- South Quarter is one of the buildings that applies green building principles located in South Jakarta. Based on the Greenship assessment standards, energy saving efforts to decrease OTTV value on some office floors are considered optimal (≤33.25W/m2), but haven’t occupied the natural lighting intensity standard (≤30%). Based on the existing design, there are things which can be optimized such as the color selection of floor, ceiling, and envelope material. The lighting optimization will certainly affect the heat that goes into the building, therefore the effort of optimizing South Quarter office façade design for the fulfillment of natural lighting intensity and OTTV value based on the Greenship criteria is important to do.This research uses descriptive-evaluative research with quantitative-qualitative approach. The evaluative research is done by controlling the building envelope design (simulation method), then observing the effects. These effects are devoted to 2 points, which are natural lighting intensity and OTTV value. The qualitative approach is done by observing the object of study.By replacing glass material, floor material, adding shading elements and light shelf, the optimization of building envelope design has increased the natural lighting intensity by 14.84-30.71% to occupy the Greenship criteria, while maintaining the OTTV standard. Key Words: natural lighting intensity, OTTV value, Greenship, material, shading, light shelf.